2018
DOI: 10.17576/jsm-2018-4701-14
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of Malaysian Apis mellifera Propolis

Abstract: Propolis is a resinous material collected by honey bees from various plant sources. The chemical constituents differ depending on the source of vegetation area. To date, no study of the chemical constituents of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
(46 reference statements)
0
2
0
1
Order By: Relevance
“…For propolis, four studies used propolis from Trigona itama and two studies used propolis from Trigona thoracica . Meanwhile, one of the studies by Tuan Ismail et al ( 15 ) mentioned the name of the bee species, which was Apis mellifera , and the other two studies did not state the types of propolis used. There was one study on bee bread that used Heterotrigona itama bee bread.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For propolis, four studies used propolis from Trigona itama and two studies used propolis from Trigona thoracica . Meanwhile, one of the studies by Tuan Ismail et al ( 15 ) mentioned the name of the bee species, which was Apis mellifera , and the other two studies did not state the types of propolis used. There was one study on bee bread that used Heterotrigona itama bee bread.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, propolis has also been shown to have promising effects in treating acne vulgaris due to its great antibacterial activity. Tuan Ismail et al ( 15 ) tested EEP and water extract (WEP) of Malaysian Apis mellifera propolis from the northern and southern regions of Peninsular Malaysia and the results demonstrated that EEP from the northern region showed the best antibacterial activity against Propionibacterium acnes with MIC values, 0.32 μg/mL, followed by EEP from the southern region, WEP from the southern region and WEP from northern region with MIC values 0.63 μg/mL, 625 μg/mL and 2,500 μg/mL, respectively. Besides, propolis can be developed into nanoparticles with chitosan since nanoparticles have recently gained attention in medicine because of their better efficacy, improved bioavailability and enhanced penetration ability ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…Propolis found in East Java, Indonesia was shown to be botanically sourced from Mangifera indica L. and Macaranga tanarius L., and Calophyllum inophyllum Linn was confirmed to be the botanical source for propolis found in Lombok, Indonesia (Mizuno et al, 2022; Trusheva et al, 2011). In the northern and southern regions of Peninsular Malaysia, the predominant botanical source was Acacia mangium and other shrubs and fruit orchards may also contribute as sources (Tuan Ismail et al, 2018).…”
Section: Properties Of Propolismentioning
confidence: 99%
“…Çok çeşitli bir bileşime sahip olan propolis, fenolik asitler, flavonoidler, terpenler gibi potansiyel olarak biyoaktif bileşikleri de içermektedir (16). Genel olarak propolis toplandığı bitki florasına bağlı olarak %40-70 reçine; %3-5 uçucu yağ; %25-30 balmumu; %5 mineral madde, protein ve vitamin gibi diğer maddelerden meydana gelmiştir (17,18). Kimyasal olarak başta pinosambrin, pinobanksin, quersetin, pinosembrin, galangin, ve kamferol olmak üzere 38 farklı flavonoid belirlenmiştir.…”
Section: Propoli̇si̇n Yapisi Ve öZelli̇kleri̇unclassified